AKUNTANSI FORENSIK: TELAAH EMPIRIS PENERAPAN DALAM KURIKULUM AKUNTANSI - Zaenal Fanani; Clarina Widyati Gunawan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2020)
The main objective of this study was to determine whether there are differences in the application of the teaching of forensic accounting in the accounting curriculum. This study uses a simple random sampling by distributing questionnaires for accounting lecturer in public and private universities with accreditation A. Observation data obtained as many as 63. The variables used were the relevance of teaching, teaching benefits, obstacles teaching, teaching materials, and learning mechanisms. Analysis techniques using Independent Sample T Test. The results showed that there is a difference between public and private universities in terms of teaching the relevance, benefits of teaching, teaching materials and learning mechanisms forensic accounting and there is no difference between public and private universities for teaching barriers forensic accounting.